Impact of Environmental Sanitation on Stunting Risk in Talagasari, Tasikmalaya - Reva Dewari Daniswara; Ade Kurniawati; Meti Patimah; Melsa Sagita Imaniar; Rissa Nuryuniarti (Media Ilmiah Kesehatan Indonesia, 2026)
Stunting is a chronic nutritional problem that affects children’s physical growth, cognitive development, learning ability, and future productivity. Indirect factors presumed to be associated with stunting include maternal parenting practices, particularly among children aged 12–59 months. This study aimed to analyze the association between maternal parenting practices and the incidence of stunting in Talagasari Urban Village, within the working area of Kawalu Public Health Center, Tasikmalaya City. A quantitative cross-sectional design was employed, with a sample of 83 children selected using stratified random sampling. Data were collected through a maternal parenting practices questionnaire and anthropometric measurements of children, then analyzed using the Chi-square test at a significance level of p < 0.05. The results showed that most mothers had good parenting practices, and the majority of children were not stunted. However, statistical analysis indicated no significant association between maternal parenting practices and the incidence of stunting. These findings suggest that stunting is influenced by other factors, including maternal nutritional status during pregnancy, socio-economic conditions, recurrent infectious diseases, and Clean and Healthy Living Behaviors (PHBS). Comprehensive stunting prevention should be implemented through nutrition education, sanitation improvement, family support, and cross-sectoral collaboration.